Age-Related Variations in the Apparent Metabolizable Energy of Meat and Bone Meal for Broilers - Mahmoud M. Khalil; M. Reza Abdollahi; Faegheh Zaefarian; Velmurugu Ravindran (Animals, 2024)
The influence of broiler age on the apparent metabolizable energy (AME) and nitrogen-corrected AME (AMEn) of meat and bone meal (MBM) was investigated. A corn–soy basal diet and an experimental diet wherein 300 g/kg of the basal diet was replaced (w/w) with MBM were developed. The diets, in pellet form, were fed to six replicate cages across six age groups, namely d 1 to 7, 8 to 14, 15 to 21, 22 to 28, 29 to 35 or 36 to 42 d post-hatch. Birds were fed either a starter diet from d 1–21 or a finisher diet from d 22–35. Basal and experimental diets were introduced on d 1, 8, 15, 22, 29 and 36 with 10 (d 1–7), 8 (d 8–14) and 6 (d 15–42) birds per replicate. Total collection of excreta was carried out during the last 4 d of each age period. A linear decrease (p < 0.001) in the retention of dry matter and nitrogen was observed with advancing age. The AMEn of MBM showed a linear increase (p < 0.05), rising from 12.56 MJ/kg during d 1–7 to 13.90 MJ/kg during d 29–35, followed by a decline to 13.41 MJ/kg during d 36–42. The current findings showed that the energy utilization of MBM increased with the advancing age of broilers. Age-dependent AMEn values of MBM may need to be considered when MBM is included in feed formulations.